The Stunted Identity of Emily Grierson in A Rose for Emily by William Faulkner - Ratna Asmarani (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2017)
AbstractThe purpose of writing this paper is to analyze the problem concerning the oppression of the female character’s identity in Faulkner’s short story entitled A Rose for Emily. The focuses are on the triggering factors of the stunted identity, the efforts to develop personal identity, and the impacts of the undeveloped personal identity. The concept of identity, James Marcia’s concept of identity statuses, and the stereotypes of the women in the nineteenth century are used as analysis tools. The result shows that if identity which should be fluid and able to develop freely is oppressed and stunted many times, the female character will be stuck in the status of “identity foreclosure”. The outcome will be unpredictable and even horrifying. The conclusion that can be drawn is that women are vulnerable to identity crisis because they are often not given chances to develop their identity freely. As a result there is a tendency for those women to do things considered perverse by the society.Keywords: identity, identity statuses, identity foreclosure